Contrasting evolutionary patterns between two haplogroups of Haematobia exigua (Diptera: Muscidae) from the mainland and islands of Southeast Asia - Low, Van Lun; Tan, T.K.; Prakash, B.K.; Vinnie-Siow, W.Y.; Tay, Sun Tee; Masmeatathip, R.; Hadi, U.K.; Lim, Yvonne Ai Lian; Chen, Chee Dhang; Norma-Rashid, Yusoff; Sofian-Azirun, Mohd (Nature Publishing Group, 2017)
Uncovering the hidden diversity and evolutionary history of arthropods of medico-veterinary importance could have significant implications for vector-borne disease control and epidemiological intervention. The buffalo fly Haematobia exigua is an obligate bloodsucking ectoparasite of livestock. As an initial step towards understanding its population structures and biogeographic patterns, we characterized partial cytochrome c oxidase subunit I (COI) and cytochrome b (Cytb) sequences of H. exigua from three distinct geographic regions in Southeast Asia. We detected two distinct mitochondrial haplogroups of H. exigua in our surveyed geographic regions. Haplogroup I is widespread in the Southeast Asian mainland whereas haplogroup II is generally restricted to the type population Java Island. Both haplogroups were detected co-occurring on Borneo Island. Additionally, both haplogroups have undergone contrasting evolutionary histories, with haplogroup I exhibited a high level of mitochondrial diversity indicating a population expansion during the Pleistocene era dating back to 98,000 years ago. However, haplogroup II presented a low level of mitochondrial diversity which argues against the hypothesis of recent demographic expansion.